Names of Diseases in the Vernacular (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Illness is a reaction of some parts of the body to damage, infection or other factors. A non-terminological name of a disease is a word or phrase associated with a non-terminological (everyday) medical lexicon, that is, synonymous with the scientific names of diseases and widely used in colloquial speech. used anemia - anemia, hepatitis - jaundice, Kreittfelidt - Jakob - cow rabies (brain decay), hallucination - delirium, vitiligo - pes, tuberculosis - tuberculosis, epilepsy - seizure, acne - dysentery, parotitis - reaction to the group of speech units or archaism Past words: hemorrhoids, diarrhea, heartburn.